Electrocoppering solution for ceramic packaging substrate and use method of electrocoppering solution

By using a copper electroplating solution with a specific composition and parameters on the UV LED package substrate, high-speed copper plating under high current density is achieved, solving the problem of long electroplating time and improving production efficiency and coating quality.

CN120844160AActive Publication Date: 2025-10-28SHENZHEN BANMING SCI & TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511355429.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-22
Publication Date
2025-10-28
Estimated Expiration
2045-09-22

AI Technical Summary

Technical Problem

In the prior art for preparing UV LED package substrate dams, the electroplating time is too long, the production efficiency is low, and the current density allowed by conventional electroplating additives is insufficient, making it difficult to meet the requirements of high-speed copper plating at high current density.

Method used

Provided is a copper electroplating solution for ceramic packaging substrates, comprising sulfuric acid, copper sulfate pentahydrate, chloride ions, an accelerator, an inhibitor, and a leveler at a specific concentration. The solution, when used in conjunction with appropriate parameters, can achieve high-speed copper plating at a high current density of 8-12 A/dm2.

Benefits of technology

By increasing the working current density during electroplating, shortening the electroplating time, and improving the efficiency of electroplating dam production, the uniformity and reliability of the plating layer are ensured to meet the needs of high-speed copper plating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120844160A_ABST
    Figure CN120844160A_ABST
Patent Text Reader

Abstract

The invention discloses a copper electroplating solution for a ceramic packaging substrate and a use method of the copper electroplating solution, and relates to the technical field of circuit board electroplating. The electrocoppering solution for the ceramic packaging substrate comprises the following components in mass concentration: 100 to 200 g / L of sulfuric acid, 100 to 200 g / L of copper sulfate pentahydrate, 50 to 80 mg / L of chloride ions, 10 to 25 mg / L of an accelerator, 200 to 2000 mg / L of an inhibitor and 10 to 20 mg / L of a leveling agent, and the accelerator is a 3-sulfur-isothiourea sodium propanesulfonate compound. According to the electro-coppering solution for the ceramic packaging substrate and the using method of the electro-coppering solution, the 3-sulfur-isothiourea sodium propanesulfonate compound in the electro-coppering solution can still keep a good accelerator function under the condition that an anode has oxygen evolution during high-current-density electroplating; the octylphenol polyoxyethylene ether and the nonylphenol polyoxyethylene ether can be uniformly dispersed on a power line in a solution at a relatively high temperature when the current density is large.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of circuit board electroplating technology, and in particular to an electroplating copper solution for ceramic packaging substrates and its application method. Background Technology

[0002] LEDs are solid-state semiconductor light-emitting devices based on the principle of PN junction electroluminescence. Different wavelength LEDs can be fabricated using different semiconductor materials. The LED chip is the key component of an LED. Ultraviolet LED chips have low quantum efficiency, which easily leads to excessive heat accumulation. If a large amount of heat is not dissipated in time, the LED junction temperature will rise. If the temperature exceeds the chip's withstand temperature, the LED's luminous efficiency will decrease rapidly, resulting in light decay, and the emission spectrum will shift. When the junction temperature reaches above 125°C, the LED may even fail.

[0003] Currently, PN junction temperatures are generally reduced by minimizing heat generation and accelerating heat dissipation. On one hand, an AlN (aluminum nitride) buffer layer is introduced onto a sapphire substrate, employing an AlN / AlGaN (aluminum nitride / galvanic nitride) superlattice structure to reduce the number of dislocations in the epitaxial material, improve quantum efficiency, and reduce heat generation. On the other hand, flip-chip UV LEDs are fabricated using flip-chip eutectic bonding technology to directly eutectic bond the UV LED chip to a high thermal conductivity packaging substrate. This reduces the thermal resistance at the packaging interface, allowing the heat generated by the chip to be effectively conducted to the packaging substrate, thus reducing the UV LED junction temperature.

[0004] Furthermore, because ultraviolet LED chips are highly sensitive to the external environment, they are easily corroded by moisture and dust, leading to performance degradation or failure. Hermetic packaging is commonly used to effectively isolate the chip from its surroundings, preventing moisture intrusion during its operational lifespan and ensuring normal chip operation and long-term reliability. Therefore, it has become one of the important development directions for ultraviolet LED packaging.

[0005] Currently, most UV LED packages commonly use epoxy resin or silicone organic materials coated on the chip surface. This packaging structure is simple, the process is mature, and the cost is relatively low. However, organic materials are difficult to guarantee reliability when operating under high-intensity UV light, humidity, and heat conditions for extended periods.

[0006] To address the challenges in UV LED chip packaging, the first step is to replace organic materials with inorganic metals. The UV LED chip is then placed inside a metal dam structure, evacuated, or filled with inert gas. A quartz glass lens is used to achieve an airtight seal, improving the reliability of the UV LED. Ceramic packaging substrates offer high circuit precision and surface flatness, allowing for the fabrication of vias to meet the requirements of flip-chip packaging, making them the preferred substrate for UV LED packaging. To achieve hermetic packaging of UV LEDs, metal dams need to be fabricated on a planar ceramic packaging substrate. This type of ceramic packaging substrate with dams is also called a three-dimensional ceramic packaging substrate. There are two main approaches to dam fabrication: 1. Fabricating independent dams, such as machining ceramic or metal materials into dam shapes and then fixing the dams to the planar packaging substrate using adhesives or welding to form a three-dimensional ceramic packaging substrate; 2. Directly fabricating dam structures on a planar packaging substrate, using techniques such as electroplating and inorganic slurry molding. Adhesive bonding is simple, low-cost, and easy for large-scale industrial production. The disadvantage is that organic adhesives will age continuously during use, and their reliability will decrease, especially under conditions of drastic temperature or humidity changes. Electroplating to prepare the dam has the advantage that the dam and the LED ceramic packaging substrate are directly electroplated together, resulting in high reliability. The disadvantage is that the dam height is generally around 300 micrometers, and the conventional electroplating time is very long, sometimes even more than ten hours, resulting in low production efficiency.

[0007] When preparing dams by electroplating, under the condition that the plating thickness is constant, the current density is inversely proportional to the electroplating time. If the electroplating time is to be shortened, the current density during electroplating must be increased. However, the allowable current density of existing copper plating additives is generally only 5 A / dm³. 2 There are virtually no electroplating additives specifically designed for high-current-density, high-speed copper plating in the production of LED packaging substrates. Developing electroplating copper solutions and their application methods for ceramic packaging substrates is an inevitable choice to adapt to the technological advancement of my country's special circuit board production. Summary of the Invention

[0008] The technical problem to be solved by this invention is: in the development of high-current-density, high-speed copper plating solutions for electroplating dam fabrication in LED ceramic packaging substrates, it is necessary to increase the allowable operating current density during electroplating and shorten the electroplating time so that the product meets the requirements of 8-12 A / dm². 2 High current density and high-speed copper plating requirements.

[0009] To address the shortcomings of existing technologies, this invention provides an electroplating copper solution for ceramic packaging substrates and its application method. By using a specific electroplating copper solution with appropriate operating parameters, the operating current density can be effectively increased, thereby improving the electroplating efficiency during the fabrication of electroplating dams.

[0010] Specifically, the following technical solutions are included: In a first aspect, a copper plating solution for ceramic packaging substrates is provided, comprising the following components by mass concentration: 100-200 g / L sulfuric acid, 100-200 g / L copper sulfate pentahydrate, 50-80 mg / L chloride ions, 10-25 mg / L accelerator, 200-2000 mg / L inhibitor, and 10-20 mg / L leveling agent; wherein the accelerator is sodium 3-thio-isothiourea propanesulfonate compound, and the inhibitor is octylphenol polyoxyethylene ether and / or nonylphenol polyoxyethylene ether.

[0011] Specifically, the accelerator is C4H 10 N2O3S2.

[0012] Furthermore, the leveling agent is 2-mercaptobenzimidazole or 2-mercaptobenzothiazole.

[0013] Furthermore, the inhibitor is octylphenol polyoxyethylene ether and nonylphenol polyoxyethylene ether, and the mass ratio of octylphenol polyoxyethylene ether to nonylphenol polyoxyethylene ether is 1:(0.5-2).

[0014] Furthermore, the mass ratio of octylphenol polyoxyethylene ether to nonylphenol polyoxyethylene ether is 1:1.

[0015] Furthermore, the electroplating copper solution for the ceramic packaging substrate comprises the following components by mass concentration: sulfuric acid 150-200 g / L, copper sulfate pentahydrate 100-150 g / L, chloride ions 50-80 mg / L, accelerator 10-25 mg / L, inhibitor 200-2000 mg / L, leveling agent 10-20 mg / L, and the balance being deionized water.

[0016] Furthermore, the electroplating copper solution for the ceramic packaging substrate is composed of the following components by mass concentration: 150 g / L sulfuric acid, 150 g / L copper sulfate pentahydrate, 70 mg / L chloride ions, 15 mg / L accelerator, 1000 mg / L inhibitor, 15 mg / L leveling agent, and the balance being deionized water.

[0017] Secondly, a method for using the copper plating solution for ceramic packaging substrates as described in the first aspect is provided, comprising the following steps: using the copper plating solution for ceramic packaging substrates as described in the first aspect to electroplate the product to be electroplated.

[0018] Preferably, the method of using the copper plating solution for ceramic packaging substrates includes the following steps: using the copper plating solution for ceramic packaging substrates, the copper plating solution for ceramic packaging substrates is allowed to flow by blowing air, and the product to be electroplated is electroplated.

[0019] Furthermore, the electroplating conditions are as follows: a DC power supply is used, and the cathode current density is 8-12 A / dm². 2 .

[0020] Furthermore, the temperature of the copper plating solution used for the ceramic packaging substrate is 30-50°C.

[0021] Furthermore, the anode for electroplating is a titanium anode with an iridium-tantalum coating, and the cathode for electroplating is the product to be electroplated.

[0022] The beneficial effects of this invention are as follows: This invention provides a copper plating solution for ceramic packaging substrates and its application method. The sodium 3-thio-isothiourea propanesulfonate compound in the copper plating solution maintains good accelerator function even under oxygen evolution conditions at the anode during high current density electroplating. Octylphenol polyoxyethylene ether and nonylphenol polyoxyethylene ether can uniformly disperse electric field lines at high current densities in solutions at relatively high temperatures (30-50°C). Furthermore, the accelerator, inhibitor, leveling agent, and other components in the copper plating solution work synergistically to achieve 8-12 A / dm². 2 High current density and high-speed copper plating requirements. Attached Figure Description

[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 A microscope image of a sample after an appearance test was performed in Example 1 of the present invention. Figure 2 This is a microscope image of the sample after the appearance test was performed in Example 2 of the present invention; Figure 3 This is a microscope image of the sample after the appearance test was performed in Example 3 of the present invention; Figure 4 This is a microscope image of the sample after the appearance test was performed in Example 4 of the present invention; Figure 5 This is a microscope image of the sample after the appearance test in Example 5 of the present invention; Figure 6 This is a microscope image of the sample after the appearance test was performed in Example 6 of the present invention; Figure 7 This is a microscope image of the sample after the appearance test was performed in Example 7 of the present invention; Figure 8 This is a microscope image of the sample after the appearance test was performed in Example 8 of the present invention; Figure 9 This is a microscope image of the sample after the appearance test was performed in Example 9 of the present invention; Figure 10 A microscope image of a sample after an appearance test was performed in Example 10 of the present invention. Figure 11 This is a microscope image of the sample after the appearance test was performed in Example 11 of the present invention; Figure 12 This is a microscope image of a sample after an appearance test was performed in Example 12 of the present invention. Figure 13 This is a microscope image of a sample after an appearance test was performed in Example 13 of the present invention. Figure 14 This is a microscope image of the sample after the appearance test was performed in Example 14 of the present invention; Figure 15 This is a microscope image of a sample after an appearance test was performed in Example 15 of the present invention. Figure 16 This is a microscope image of the sample after the appearance test was performed in Example 16 of the present invention. Figure 17 This is a microscope image of the sample after the appearance test of Comparative Example 1 of the present invention. Figure 18 This is a microscope image of the sample after the appearance test of Comparative Example 2 of the present invention. Figure 19 This is a microscope image of the sample after the appearance test of Comparative Example 3 of the present invention. Figure 20 This is a microscope image of the sample after the appearance test of Comparative Example 4 of the present invention. Figure 21 This is a microscope image of the sample after the appearance test of Comparative Example 5 of the present invention. Figure 22 This is a microscope image of the sample after the appearance test of Comparative Example 6 of the present invention. Figure 23 This is a microscope image of the sample after the appearance test of Comparative Example 7 of the present invention. Figure 24 This is a microscope image of the sample after the appearance test of Comparative Example 8 of the present invention. Figure 25 This is a microscope image of the sample after the appearance test of Comparative Example 9 of the present invention. Figure 26 This is a microscope image of the sample after the appearance test of Comparative Example 10 of the present invention. Figure 27 This is a microscope image of the sample after the appearance test of Comparative Example 11 of the present invention. Figure 28 This is a microscope image of the sample after the appearance test of Comparative Example 12 of the present invention. Figure 29This is a microscope image of the sample after the appearance test of Comparative Example 13 of the present invention. Figure 30 This is a microscope image of the sample after the appearance test of Comparative Example 14 of the present invention. Figure 31 This is a microscope image of the sample after the appearance test of Comparative Example 15 of the present invention. Figure 32 This is a microscope image of the sample after the appearance test of Comparative Example 16 of the present invention. Detailed Implementation

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] It should be understood that, when used in this specification and the appended claims, the terms "comprising" and "including" indicate the presence of the described features, integrals, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integrals, steps, operations, elements, components and / or collections thereof.

[0027] It should also be understood that the terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. As used in this specification and the appended claims, the singular forms “a,” “an,” and “the” are intended to include the plural forms unless the context clearly indicates otherwise.

[0028] It should also be further understood that the term "and / or" as used in this specification and the appended claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes such combinations.

[0029] To better understand the technical content of the present invention, the technical solution of the present invention will be further introduced and explained below with reference to specific embodiments.

[0030] The preparation method of the electroplating copper solution for ceramic packaging substrates in the examples and comparative examples includes the following steps: mixing sulfuric acid, copper sulfate pentahydrate, chloride ions, accelerator, inhibitor, leveling agent and the balance deionized water to obtain the solution.

[0031] Example 1 A copper plating solution for ceramic packaging substrates comprises the following components by mass concentration: 150 g / L sulfuric acid, 150 g / L copper sulfate pentahydrate, 70 mg / L chloride ions, 15 mg / L accelerator, 1000 mg / L inhibitor, 15 mg / L leveling agent, and the balance being deionized water; the accelerator is sodium 3-thio-isothiourea propanesulfonate compound (C4H4H4O2). 10 The inhibitor is octylphenol polyoxyethylene ether and nonylphenol polyoxyethylene ether, with a mass ratio of octylphenol polyoxyethylene ether to nonylphenol polyoxyethylene ether of 1:1; the leveling agent is 2-mercaptobenzimidazole.

[0032] The method for using the copper plating solution for ceramic packaging substrates includes the following steps: A copper plating solution for a ceramic packaging substrate, applied at 40°C, is added to an electroplating tank. Titanium anodes coated with iridium-tantalum are placed at both ends of the tank as anodes. The tank is agitated by blowing air into the center at a rate of 2 L / min. This airflow allows the copper plating solution to flow onto the ceramic packaging substrate, thus electroplating the product. The cathode is the product itself. The electroplating conditions are: DC power supply, cathode current density of 10 A / dm³. 2 .

[0033] The copper plating solutions for ceramic packaging substrates of Examples 2-6 were prepared according to the composition and usage method of the copper plating solution for ceramic packaging substrates in Table 1 below, and electroplating was performed according to the usage method. Table 1 shows the differences between Examples 2-6 and Example 1. The composition and usage method of the copper plating solution for ceramic packaging substrates not shown in Table 1 are the same as those in Example 1.

[0034] Table 1. Composition and application method of copper plating solution for ceramic packaging substrates in Examples 2-6

[0035] The accelerator listed in Table 1 is sodium 3-thio-isothiourea propanesulfonate compound (C4H). 10 (N2O3S2), the inhibitor ratio is the mass ratio of octylphenol polyoxyethylene ether to nonylphenol polyoxyethylene ether, leveling agent 1 is 2-mercaptobenzimidazole, and leveling agent 2 is 2-mercaptobenzothiazole. Current density and solution temperature refer to the electroplating conditions and the temperature of the electroplating copper solution for ceramic packaging substrates, respectively, in the usage method of the copper plating solution for ceramic packaging substrates.

[0036] The copper plating solutions for ceramic packaging substrates of Examples 7-11 were prepared according to the composition and usage method of the copper plating solution for ceramic packaging substrates in Table 2 below, and electroplating was performed according to the usage method. Table 2 shows the differences between Examples 7-11 and Example 1. The composition and usage method of the copper plating solutions for ceramic packaging substrates not mentioned in the table are the same as those in Example 1.

[0037] Table 2. Composition and application method of copper plating solution for ceramic packaging substrates in Examples 7-11

[0038] The accelerator listed in Table 2 is sodium 3-thio-isothiourea propanesulfonate compound (C4H). 10 (N2O3S2), the inhibitor ratio is the mass ratio of octylphenol polyoxyethylene ether to nonylphenol polyoxyethylene ether, leveling agent 1 is 2-mercaptobenzimidazole, and leveling agent 2 is 2-mercaptobenzothiazole. Current density and solution temperature refer to the electroplating conditions and the temperature of the electroplating copper solution for ceramic packaging substrates, respectively, in the usage method of the copper plating solution for ceramic packaging substrates.

[0039] The copper plating solutions for ceramic packaging substrates of Examples 12-16 were prepared according to the composition and usage method of the copper plating solution for ceramic packaging substrates in Table 3 below, and electroplating was performed according to the usage method. Table 3 shows the differences between Examples 12-16 and Example 1. The composition and usage method of the copper plating solution for ceramic packaging substrates not mentioned in the table are the same as those in Example 1.

[0040] Table 3. Composition and application method of copper plating solution for ceramic packaging substrates in Examples 12-16

[0041] The accelerator listed in Table 3 is sodium 3-thio-isothiourea propanesulfonate compound (C4H). 10 (N2O3S2), the inhibitor ratio is the mass ratio of octylphenol polyoxyethylene ether to nonylphenol polyoxyethylene ether, leveling agent 1 is 2-mercaptobenzimidazole, and leveling agent 2 is 2-mercaptobenzothiazole. Current density and solution temperature refer to the electroplating conditions and the temperature of the electroplating copper solution for ceramic packaging substrates, respectively, in the usage method of the copper plating solution for ceramic packaging substrates.

[0042] The copper plating solutions for ceramic packaging substrates of Comparative Examples 1-5 were prepared according to the composition and usage method of the copper plating solution for ceramic packaging substrates shown in Table 4 below, and electroplating was performed according to the usage method. Table 4 shows the differences between Comparative Examples 1-5 and Example 1. The composition and usage method of the copper plating solutions for ceramic packaging substrates not shown in the table are the same as those in Example 1.

[0043] Table 4. Composition and application methods of copper plating solutions for ceramic packaging substrates in Comparative Examples 1-5

[0044] The accelerator listed in Table 4 is sodium 3-thio-isothiourea propanesulfonate compound (C4H). 10(N2O3S2), the inhibitor ratio is the mass ratio of octylphenol polyoxyethylene ether to nonylphenol polyoxyethylene ether, leveling agent 1 is 2-mercaptobenzimidazole, and leveling agent 2 is 2-mercaptobenzothiazole. Current density and solution temperature refer to the electroplating conditions and the temperature of the electroplating copper solution for ceramic packaging substrates, respectively, in the usage method of the copper plating solution for ceramic packaging substrates.

[0045] The copper plating solutions for ceramic packaging substrates of Comparative Examples 6-10 were prepared according to the composition and usage method of the copper plating solution for ceramic packaging substrates in Table 5 below, and electroplating was performed according to the usage method. Table 5 shows the differences between Comparative Examples 6-10 and Example 1. The composition and usage method of the copper plating solutions for ceramic packaging substrates not mentioned in the table are the same as those in Example 1.

[0046] Table 5. Composition and application method of copper plating solution for ceramic packaging substrates in Comparative Examples 6-10

[0047] The accelerator listed in Table 5 is sodium 3-thio-isothiourea propanesulfonate compound (C4H). 10 (N2O3S2), the inhibitor ratio is the mass ratio of octylphenol polyoxyethylene ether to nonylphenol polyoxyethylene ether, leveling agent 1 is 2-mercaptobenzimidazole, and leveling agent 2 is 2-mercaptobenzothiazole. Current density and solution temperature refer to the electroplating conditions and the temperature of the electroplating copper solution for ceramic packaging substrates, respectively, in the usage method of the copper plating solution for ceramic packaging substrates.

[0048] The copper plating solutions for ceramic packaging substrates of Comparative Examples 11-16 were prepared according to the composition and usage method of the copper plating solution for ceramic packaging substrates in Table 6 below, and electroplating was performed according to the usage method. Table 6 shows the differences between Comparative Examples 11-16 and Example 1. The composition and usage method of the copper plating solutions for ceramic packaging substrates not mentioned in the table are the same as those in Example 1.

[0049] Table 6. Composition and application method of copper plating solution for ceramic packaging substrates in Comparative Examples 11-16

[0050] The accelerator listed in Table 6 is sodium 3-thio-isothiourea propanesulfonate compound (C4H). 10 (N2O3S2), the inhibitor ratio is the mass ratio of octylphenol polyoxyethylene ether to nonylphenol polyoxyethylene ether, leveling agent 1 is 2-mercaptobenzimidazole, and leveling agent 2 is 2-mercaptobenzothiazole. Current density and solution temperature refer to the electroplating conditions and temperature of the copper plating solution for ceramic packaging substrates, respectively, in the application method of the copper plating solution for ceramic packaging substrates. Comparative Examples 15 and 16 in Table 6 use phosphorus copper anodes as the anode.

[0051] Performance Test: I. Sample Appearance Test: The product to be electroplated is a test plate to be plated. The test plate to be plated is pretreated by degreasing, micro-etching, and activation in a dilute sulfuric acid solution, and then is respectively placed into the liquid in the above electroplating bath (the electroplated copper solution for the ceramic packaging substrate in the embodiment or the comparative example), and electroplating is carried out using the usage method of the electroplated copper solution for the ceramic packaging substrate in the embodiment or the comparative example (vertically placed in the middle position of the electroplating bath) until the coating thickness reaches 300 microns. The electroplated samples are respectively subjected to appearance inspection and microscopic observation. It is required that the sample appearance is uniform, bright, flat, without pinholes and copper particles.

[0052] II. Tensile Strength and Elongation at Break Test: A stainless steel plate is used instead of the test plate in the sample appearance test as the product to be electroplated, and the other conditions are the same as those in the sample appearance test. The coating thickness is plated to 60 microns, and copper foils are made by peeling from the stainless steel plate, and the copper foils are used for tensile strength and elongation at break tests. The qualified criteria are that the tensile strength is greater than 248 MPa and the elongation at break is greater than 10%.

[0053] The electroplated copper solutions for the ceramic packaging substrates in Examples 1-5 are subjected to performance tests, and the test results are shown in Table 7 below: Table 7 Performance Test Results of Electroplated Copper Solutions for Ceramic Packaging Substrates in Examples 1-5

[0054] Figure 1 Microscopic image of the sample after the sample appearance test in Example 1 of the present invention; Figure 2 Microscopic image of the sample after the sample appearance test in Example 2 of the present invention; Figure 3 Microscopic image of the sample after the sample appearance test in Example 3 of the present invention; Figure 4 Microscopic image of the sample after the sample appearance test in Example 4 of the present invention; Figure 5 Microscopic image of the sample after the sample appearance test in Example 5 of the present invention.

[0055] The electroplated copper solutions for the ceramic packaging substrates in Examples 6-10 are subjected to performance tests, and the test results are shown in Table 8 below: Table 8 Performance Test Results of Electroplated Copper Solutions for Ceramic Packaging Substrates in Examples 6-10

[0056] Figure 6 Microscopic image of the sample after the sample appearance test in Example 6 of the present invention; Figure 7 Microscopic image of the sample after the sample appearance test in Example 7 of the present invention; Figure 8 Microscopic image of the sample after the sample appearance test in Example 8 of the present invention; Figure 9This is a microscope image of the sample after the appearance test was performed in Example 9 of the present invention; Figure 10 This is a microscope image of the sample after the appearance test was performed in Example 10 of the present invention.

[0057] The ceramic packaging substrates of Examples 11-16 were subjected to performance tests using an electroplated copper solution. The test results are shown in Table 9 below. Table 9 Performance test results of copper plating solutions for ceramic packaging substrates in Examples 11-16

[0058] Figure 11 This is a microscope image of the sample after the appearance test was performed in Example 11 of the present invention; Figure 12 This is a microscope image of a sample after an appearance test was performed in Example 12 of the present invention. Figure 13 This is a microscope image of a sample after an appearance test was performed in Example 13 of the present invention. Figure 14 This is a microscope image of the sample after the appearance test was performed in Example 14 of the present invention; Figure 15 This is a microscope image of a sample after an appearance test was performed in Example 15 of the present invention. Figure 16 This is a microscope image of the sample after the appearance test was performed in Example 16 of the present invention.

[0059] The ceramic packaging substrates of Comparative Examples 1-5 were subjected to performance tests using an electroplated copper solution. The test results are shown in Table 10 below. Table 10 Performance test results of copper plating solution for ceramic packaging substrates in Comparative Examples 1-5

[0060] Figure 17 This is a microscope image of the sample after the appearance test of Comparative Example 1 of the present invention. Figure 18 This is a microscope image of the sample after the appearance test of Comparative Example 2 of the present invention. Figure 19 This is a microscope image of the sample after the appearance test of Comparative Example 3 of the present invention. Figure 20 This is a microscope image of the sample after the appearance test of Comparative Example 4 of the present invention. Figure 21 This is a microscope image of the sample after the appearance test of Comparative Example 5 of this invention.

[0061] As can be seen from Table 10, the performance test results of the following solutions are all unsatisfactory: copper plating solution for ceramic packaging substrates prepared with sulfuric acid (which is not within the mass concentration range specified in this invention) (Comparative Example 1), copper plating solution for ceramic packaging substrates prepared with copper sulfate pentahydrate (which is not within the mass concentration range specified in this invention) (Comparative Example 2), copper plating solution for ceramic packaging substrates prepared with chloride ions (which is not within the mass concentration range specified in this invention) (Comparative Example 3), copper plating solution for ceramic packaging substrates prepared with a leveling agent (which is not within the type specified in this invention) (Comparative Example 4), and copper plating solution for ceramic packaging substrates prepared with an accelerator (which is not within the mass concentration range specified in this invention) (Comparative Example 5).

[0062] The ceramic packaging substrates of Comparative Examples 6-10 were subjected to performance tests using an electroplated copper solution. The test results are shown in Table 11 below. Table 11 Performance test results of copper plating solution for ceramic packaging substrates in Comparative Examples 6-10

[0063] Figure 22 This is a microscope image of the sample after the appearance test of Comparative Example 6 of the present invention. Figure 23 This is a microscope image of the sample after the appearance test of Comparative Example 7 of the present invention. Figure 24 This is a microscope image of the sample after the appearance test of Comparative Example 8 of the present invention. Figure 25 This is a microscope image of the sample after the appearance test of Comparative Example 9 of the present invention. Figure 26 This is a microscope image of the sample after the appearance test of Comparative Example 10 of the present invention.

[0064] As can be seen from Table 11, the performance test results of the electroplating copper solution for ceramic packaging substrates prepared with accelerators not within the mass concentration range limited by the present invention (Comparative Example 6), the electroplating copper solution for ceramic packaging substrates prepared with inhibitors not within the mass concentration range limited by the present invention (Comparative Example 7, Comparative Example 8), and the electroplating copper solution for ceramic packaging substrates prepared with octylphenol polyoxyethylene ether and nonylphenol polyoxyethylene ether not within the mass ratio range limited by the present invention (Comparative Example 9, Comparative Example 10) are all unsatisfactory.

[0065] The ceramic packaging substrates of Comparative Examples 11-16 were subjected to performance tests using an electroplated copper solution. The test results are shown in Table 12 below. Table 12 Performance test results of copper plating solution for ceramic packaging substrates in Comparative Examples 11-16

[0066] Figure 27 This is a microscope image of the sample after the appearance test of Comparative Example 11 of the present invention. Figure 28This is a microscope image of the sample after the appearance test of Comparative Example 12 of the present invention. Figure 29 This is a microscope image of the sample after the appearance test of Comparative Example 13 of the present invention. Figure 30 This is a microscope image of the sample after the appearance test of Comparative Example 14 of the present invention. Figure 31 This is a microscope image of the sample after the appearance test of Comparative Example 15 of the present invention. Figure 32 This is a microscope image of the sample after the appearance test of Comparative Example 16 of the present invention.

[0067] As can be seen from Table 12, the performance test results of the copper plating solution for ceramic packaging substrates prepared using a leveling agent outside the mass concentration range defined in this invention (Comparative Examples 11 and 12) are all unsatisfactory. The performance test results of electroplating using a current density outside the range defined in this invention (in the method of using the copper plating solution for ceramic packaging substrates) (Comparative Examples 13 and 14) are also unsatisfactory. The performance test results of electroplating using an anode type outside the range defined in this invention (in the method of using the copper plating solution for ceramic packaging substrates) (Comparative Examples 15 and 16) are also unsatisfactory.

[0068] In summary, this invention provides a copper plating solution for ceramic packaging substrates and its application method. The sodium 3-thio-isothiourea propanesulfonate compound in the copper plating solution maintains good accelerator function even under oxygen evolution conditions at the anode during high current density electroplating. Octylphenol polyoxyethylene ether and nonylphenol polyoxyethylene ether can uniformly disperse electric field lines at high current densities in solutions at relatively high temperatures (30-50°C). Furthermore, the accelerator, inhibitor, leveling agent, and other components in the copper plating solution work synergistically to achieve 8-12 A / dm². 2 High current density and high-speed copper plating requirements.

[0069] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should all be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A copper plating solution for ceramic packaging substrates, characterized in that, It comprises the following components at mass concentrations: sulfuric acid 100-200 g / L, copper sulfate pentahydrate 100-200 g / L, chloride ions 50-80 mg / L, accelerator 10-25 mg / L, inhibitor 200-2000 mg / L, and leveling agent 10-20 mg / L; wherein the accelerator is sodium 3-thio-isothiourea propanesulfonate compound, and the inhibitor is octylphenol polyoxyethylene ether and / or nonylphenol polyoxyethylene ether.

2. The copper plating solution for ceramic packaging substrates as described in claim 1, characterized in that, The leveling agent is 2-mercaptobenzimidazole or 2-mercaptobenzothiazole.

3. The copper plating solution for ceramic packaging substrates as described in claim 2, characterized in that, The inhibitors are octylphenol polyoxyethylene ether and nonylphenol polyoxyethylene ether, with a mass ratio of octylphenol polyoxyethylene ether to nonylphenol polyoxyethylene ether of 1:(0.5-2).

4. The copper plating solution for ceramic packaging substrates as described in claim 3, characterized in that, The mass ratio of octylphenol polyoxyethylene ether to nonylphenol polyoxyethylene ether is 1:

1.

5. The copper plating solution for ceramic packaging substrates as described in claim 1, characterized in that, It consists of the following components in mass concentration: sulfuric acid 150-200 g / L, copper sulfate pentahydrate 100-150 g / L, chloride ion 50-80 mg / L, accelerator 10-25 mg / L, inhibitor 200-2000 mg / L, leveling agent 10-20 mg / L, and the balance is deionized water.

6. The copper plating solution for ceramic packaging substrates as described in claim 5, characterized in that, It consists of the following components in mass concentration: sulfuric acid 150 g / L, copper sulfate pentahydrate 150 g / L, chloride ion 70 mg / L, accelerator 15 mg / L, inhibitor 1000 mg / L, leveling agent 15 mg / L, and the balance is deionized water.

7. The method of using the copper plating solution for ceramic packaging substrates as described in any one of claims 1-6, characterized in that, Includes the following steps: The product to be electroplated is electroplated using the copper plating solution for ceramic packaging substrates as described in any one of claims 1-6.

8. The method of using the copper plating solution for ceramic packaging substrates as described in claim 7, characterized in that, The electroplating conditions are as follows: a DC power supply is used, and the cathode current density is 8-12 A / dm³. 2 .

9. The method of using the copper plating solution for ceramic packaging substrates as described in claim 8, characterized in that, The temperature of the copper plating solution used for the ceramic packaging substrate is 30-50℃.

10. The method of using the electroplating copper solution for ceramic packaging substrates as described in claim 9, characterized in that, The anode for electroplating is a titanium anode with an iridium-tantalum coating, and the cathode for electroplating is the product to be electroplated.

Citation Information

Patent Citations

  • Leveling agent for blind hole all-copper electroplating, preparation method of leveling agent and electroplating solution

    CN110642731A

  • Electrolyte for manufacturing electrolyte copper foil and application of electrolyte

    CN114182310A

  • Additive capable of improving oxidation resistance of ultrathin copper foil and copper foil produced by additive

    CN119800459A